The Dual Burden: Impact of Student Security Duties on Learning Quality in Indonesian Islamic Boarding School Context - Indah Puspita, Syahvira; Haris, Abd.; Sudirman; Aisyah binti Samudin, Siti; Qomaruz Zaman, Jamrud (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
The security santri system is still used by pesantren in Indonesia as a form of cultural preservation. However, many modern boarding schools today try to modify this system by imposing it on santri, who are still students/not yet graduated. This raises important questions about the quality of their learning because they have to bear double duties. To answer this hypothesis, a sample is needed in the form of the application of the security santri system with the status of students. This research is a qualitative study with data collection techniques in the form of interviews, observation, and documentation. The data analysis method in this research uses the descriptive analysis method. The result of this research is that the security santri system is not suitable for charging santri who are students. The security santri have a significant problem in the form of a busy schedule that reduces their rest time. Therefore, they often fall asleep during Dīnīyyah learning and formal high school, which causes their academic performance to decline. In addition, security santri who are less equipped with learning knowledge and age equality factors cause a lack of authority by their peers so that bullying arises as a form of dissatisfaction with their performance. This bullying ultimately causes the mentality of the security santri to fall, which then affects the quality of their learning.